Differential microRNA profiles of intramuscular and secreted extracellular vesicles in human tissue-engineered muscle - Vann, Christopher G; Zhang, Xin; Khodabukus, Alastair; Orenduff, Melissa C.; Chen, Yu-Hsiu; Corcoran, David L.; Truskey, George A.; Bursac, Nenad; Kraus, Virginia B. (Frontiers in Physiology, 2022)
Exercise affects the expression of microRNAs (miR/s) and muscle-derived extracellular vesicles (EVs). To evaluate sarcoplasmic and secreted miR expression in human skeletal muscle in response to exercise-mimetic contractile activity, we utilized a three-dimensional tissue-engineered model of human skeletal muscle (“myobundles”). Myobundles were subjected to three culture conditions: no electrical stimulation (CTL), chronic low frequency stimulation (CLFS), or intermittent high frequency stimulation (IHFS) for 7 days. RNA was isolated from myobundles and from extracellular vesicles (EVs) secreted by myobundles into culture media; miR abundance was analyzed by miRNA-sequencing. We used edgeR and a within-sample design to evaluate differential miR expression and Pearson correlation to evaluate correlations between myobundle and EV populations within treatments with statistical significance set at p<0.05. Numerous miRs were differentially expressed between myobundles and EVs; 116 miRs were differentially expressed within CTL, 3 within CLFS, and 2 within IHFS. Additionally, 25 miRs were significantly correlated (18 in CTL, 5 in CLFS, 2 in IHFS) between myobundles and EVs. Electrical stimulation resulted in differential expression of 8 miRs in myobundles and only 1 miR in EVs. Several KEGG pathways, known to play a role in regulation of skeletal muscle, were enriched, with differentially overrepresented miRs between myobundle and EV populations identified using miEAA. Together, these results demonstrate that in vitro exercise-mimetic contractile activity of human engineered muscle affects both their expression of miRs and number of secreted EVs. These results also identify novel miRs of interest for future studies of the role of exercise in organ-organ interactions in vivo.